Transgender Law in India: A Legal Conundrum (Global Journal of Human-Social Science, 2020)
The apathy of the transgender community in India is no exception to the general state of affairs across the world. Yet, the irony here is that India that has had a glorious history of the transgender community who commanded respect is now reduced to treatment worse than 'lower animals'. The colonial history has contributed significantly to this hatred and the historical injustices have not been done away with even today. The present day government has enacted a legislation that attempts to provide a sigh of relief. But, it has immense flaws underneath its glossy cover. The paper attempts to take a critical perspective of the law that points at missed opportunities that the law could have addressed and hence the ignorance of the government of the ground realities bothering the transgender community. It is unfortunate that the legislature failed to incorporate the demands of the community that it addresses. It also failed to acknowledge the sensitiveness of the issue and applied the same formulae that it adopts for all other laws without realizing that this will ultimately collapse the objectives of the law.
Keywords: transgender; reservations; criminal acts; law; bill; policy